Combinations of early generation antibiotics and antimicrobial peptides are effective against a broad spectrum of bacterial biothreat agents. (May 2020) - Cote, Christopher K.; Blanco, Irma I.; Hunter, Melissa; Shoe, Jennifer L.; Klimko, Christopher P.; Panchal, Rekha G.; Welkos, Susan L.
Abstract: The misuse of infectious disease pathogens as agents of deliberate attack on civilians and military personnel is a serious national security concern, which is exacerbated by the emergence of natural or genetically engineered multidrug resistant strains. In this study, the therapeutic potential of combinations of an antibiotic and a broad-spectrum antimicrobial peptide (AMP) was evaluated against five bacterial biothreats, the etiologic agents of glanders ( Burkholderia mallei ), melioidosis ( Burkholderia pseudomallei ), plague ( Yersinia pestis ), tularemia ( Francisella tularensis ), and anthrax ( Bacillus anthracis ). The therapeutics included licensed early generation antibiotics which are now rarely used. Three antibiotics and one 24- amino acid AMP were selected based on MIC assay data. Combinations of the AMP and tigecycline, minocycline, or novobiocin were screened for synergistic activity by checkerboard MIC assay. The combinations each enhanced the susceptibility of several strains. The tetracycline-peptide combinations increased the sensitivities of Y. pestis, F. tularensis, B. anthracis and B. pseudomallei, and the novobiocin-AMP combination augmented the sensitivity of all five. In time-kill assays, down-selected combinations of the peptide and minocycline or tigecycline enhanced killing of B. anthracis, Y. pestis, F. tularensis, and Burkholderia mallei but not B. pseudomallei . The novobiocin-AMP pair significantly reduced viability of all strains except B. mallei, which was very sensitive to the antibiotic alone. The results suggested that antibiotic-AMP combinations are useful tools for combating diverse pathogens. Future studies employing cell culture and animal models will utilize virulent strains of the agents to investigate the in vivo availability, host cytotoxicity, and protective efficacy of these therapeutics. Highlights: The adversarial use of infectious disease pathogens as bioterror tools, and the emergence of multidrug resistant pathogens, are major public health and security concerns. Combinations of underutilized antibiotics and antimicrobial peptides (AMP) were evaluated as potentially effective therapies against surrogate strains of five diverse bacterial biothreats. Specific combinations of a 24-amino acid peptide and one of three antibiotics (two tetracyclines or novobiocin) enhanced the antimicrobial susceptibility of the agents of plague, anthrax, tularemia, and melioidosis. The data supported the proposition that antibiotic-AMP combinations are useful countermeasures for combating diverse biothreat pathogens.